Improving Business Performance Using Financial Planning Toward Electrical & Mechanical Industry: Case Study of CV. Jogi Teknik - Samantha, Afra (Universitas Muhammadiyah Surakarta, 2023)
The Micro, Small and Medium Enterprise (MSMEs) sector which is engaged in the service, maintenance and installation of boilers often faces a series of challenges that hinder its growth and sustainability. The main challenge faced by MSMEs in this industry is the lack of access to finance (Board of Governors of the Federal Reserve System, 2019). CV. Jogi Teknik has experienced a decrease as shown by the gross profit margin on CV. Jogi Teknik is 24.9% in 2020, with an increase of 10.1% in 2021. Unfortunately, the conditions did not last long, where CV. Jogi Teknik experienced a significant decrease in Gross Profit Margin of up to 7.8%. According to NYU Stern School of Business data for 2023, CV has a gross profit margin. Currently the gross profit margin from CV. Jogi Teknik is lower than the electricity industry average. Researchers used a quantitative approach by processing data on the financial history of CV. Jogi Teknik and secondary data from journals, books, articles, and literature reviews. In generating data, researchers used an analysis of internal business conditions with financial reports, SWOT analysis, and business model canvas analysis. Meanwhile, to analyse the external conditions of the business using competitor analysis and competitor mapping. The results of this study want to show that CV. Jogi Teknik has low financial performance in 2022. After conducting an evaluation, to improve CV. Jogi Teknik financial performance, this company is feasible in three scenarios based on the NPV, IRR, and payback period that can be used as an optimal plan to run this business for the next five years.